Real-World Treatment Patterns, Outcomes, and Healthcare Resource Utilization in Relapsed or Refractory Multiple Myeloma: Evidence from a Medical Record Review in France - Huamao Mark Lin; Keith L. Davis; James A. Kaye; Katarina Luptakova; Saurabh P. Nagar; Mohamad Mohty (Advances in Hematology)
Background. Limited data are available from real-world practices in Europe describing prevailing treatment patterns and outcomes in relapsed/refractory multiple myeloma (RRMM), particularly by cytogenetic risk. Methods. A retrospective medical record review was conducted in 200 RRMM patients in France. From first relapse, patients were assessed on second-/third-line treatments, progression-free survival (PFS), overall survival (OS), and healthcare utilization. Results. Fifty-five high risk and 113 standard risk patients were identified. Overall, 192 patients (96%) received second-line therapy after relapse. Lenalidomide-based regimens were most common (>50%) in second line. Hospitalization incidence in high risk patients was approximately twice that of standard risk patients. From Kaplan-Meier estimation, median (95% CI) second-line PFS was 21.4 (17.5, 25.0) months (by high versus standard risk: 10.6 [6.4, 17.0] versus 28.7 [22.1, 37.3] months). Among second-line recipients, 47.4% were deceased at data collection. Median second-line OS was 59.4 (38.8, NE) months (by high versus standard risk: 36.5 [17.4, 50.6] versus 73.6 [66.5, NE] months). Conclusions. The prognostic importance of cytogenetic risk in RRMM was apparent, whereby high (versus standard) risk patients had decidedly shorter PFS and OS. Frequent hospitalizations indicated potentially high costs associated with RRMM, particularly for high risk patients. These findings may inform economic evaluations of RRMM therapies.